2016
DOI: 10.15252/embj.201593070
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonuclear messenger PRR 7 inhibits c‐Jun ubiquitination and regulates NMDA ‐mediated excitotoxicity

Abstract: Elevated c-Jun levels result in apoptosis and are evident in neurodegenerative disorders such as Alzheimer's disease and dementia and after global cerebral insults including stroke and epilepsy. NMDA receptor (NMDAR) antagonists block c-Jun upregulation and prevent neuronal cell death following excitotoxic insults. However, the molecular mechanisms regulating c-Jun abundance in neurons are poorly understood. Here, we show that the synaptic component Proline rich 7 (PRR7) accumulates in the nucleus of hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 56 publications
5
38
1
Order By: Relevance
“…Differently labeled samples of biological replicates were hybridized over night with Agilent 60 mer 4x44k whole genome rat V2 arrays (#G2519F). Our optimized protocol [27] and the "multiple yellow" strategy [28] were used to profile each "condition"…”
Section: Assessment Of Right Ventricular Hypertrophy (Rvh)mentioning
confidence: 99%
“…Differently labeled samples of biological replicates were hybridized over night with Agilent 60 mer 4x44k whole genome rat V2 arrays (#G2519F). Our optimized protocol [27] and the "multiple yellow" strategy [28] were used to profile each "condition"…”
Section: Assessment Of Right Ventricular Hypertrophy (Rvh)mentioning
confidence: 99%
“…The authors then demonstrated that RNF10 translocates to the nucleus during LTP to regulate gene expression. Similarly, PRR7 was previously identified in the postsynaptic density, and then recently shown to translocate to the nucleus following NMDAR activation, where it enhances c-Jun-dependent transcriptional activity during excitotoxicity [18,21]. These studies used proteomic profiling of synapses in combination with predicted nuclear localization data to contribute to the growing body of work identifying the population of proteins that undergo activity-dependent translocation.…”
Section: Signaling From the Post-synaptic Compartment To The Nucleusmentioning
confidence: 97%
“…Several novel synaptonuclear signaling proteins have been identified by characterizing the proteome of excitatory synapses and the interactome of NMDA receptors [18-21]. These systematic approaches allow for the identification of proteins with putative nuclear localization signals (NLS) within the synapse.…”
Section: Signaling From the Post-synaptic Compartment To The Nucleusmentioning
confidence: 99%
“…We applied an optimized protocol [47] for RNA extraction (Qiagen RNeasy mini-kit), reverse transcription (adding fluorescent tags) and hybridization onto Agilent G2519F 60mer two-colour gene expression rat 4×44k arrays in the "multiple yellow" design that provides maximum flexibility in comparing the conditions and 100% usage of the resources [48]. RNA concentrations before and after reverse transcription were estimated with a NanoDrop ND2000 Spectrophotometer, and purity was assessed with Agilent RNA 6000 Nano kit in an Agilent 2100 Bioanalyzer.…”
Section: Microarray Gene Expressionmentioning
confidence: 99%